Peningkatan hasil belajar siswa dalam pembelajaran IPS menggunakan pendekatan ctl kelas V SD Angkasa 2 Lanud Padang - Ferhia, Azky; Farida S, Farida S; Amerta, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Abstract This research is conducted by the low learning outcomes of student in learningsosial science at class 5 of elementary school 2 Lanud Padang. This is because learning is still a teacher centered. The purpose of this study is to improve student learning outcomes by using tehe ctl approach in learning social science. The type of this research is classroom action research with research subjects are teacher and student of grade 5 at elementary school 2 lanud padang. The result showe an improvement in terms of A) RPP cycle 1 was 80,35 % and cycle 2 was 96,42% B) implementation of teacher activities in cycle 1 avereged 83,33% in cycle 2 an average of 94,44 % C) The implementation of student activities in cycle 1 averaged 83,33% in cycle 2 an average 94,44% D) assasment of student learning outcomes in cycle 1 on average 78,67% an in cycle 2 93,14% this is can be concluded that the application of the ctl approach in learning social science can improve student learning outcomes. Keywords: Learning Outcomes, ctl approach